Health, longevity and pension reform - Tobias Laun; Simen Markussen; Trond Christian Vigtel; Johanna Wallenius (Uppsala University, Department of Economics, 2018)
In this paper, we study alternative pension reforms designed to achieve fiscal sustainability in the face of demographic change. We are particularly interested in the heterogeneous effects across demographic groups, as improvements in health and longevity have not been uniform across the population. To this end, we develop a dynamic, structural life cycle model of heterogeneous agents who face health, mortality and income risk. We consider the following policy reform measures: (1) increasing the early access age to pensions, (2) raising income taxes, (3) lowering pension benefits and (4) lowering pension and disability benefits. We find that, of the considered policies, proportionally lowering pension and disability benefits results in the highest average welfare and the lowest degree of inequality. It is also successful at boosting employment, particularly among the less educated.
urn:nbn:se:uu:diva-354337
Keywords: E24; J22; J26; 330; Life cycle; Retirement; Disability insurance; Health